(untitled) (Czech Journal of International Relations, 2008)
Bjørn Olav Utvik: The Pious Road to Development. Islamist Economics in Egypt. 1st ed. London: Hurst & Company, 2006, XI + 287 stran, ISBN 1-85065-760-2 (signatura knihovny ÚMV 52 972).